2019
DOI: 10.1186/s12870-019-1685-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear regression models for time to flowering in wild chickpea combine genetic and climatic factors

Abstract: BackgroundAccurate prediction of crop flowering time is required for reaching maximal farm efficiency. Several models developed to accomplish this goal are based on deep knowledge of plant phenology, requiring large investment for every individual crop or new variety. Mathematical modeling can be used to make better use of more shallow data and to extract information from it with higher efficiency. Cultivars of chickpea, Cicer arietanum, are currently being improved by introgressing wild C. reticulatum biodive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…Since C1 was mostly composed of the wild genotypes (i.e. 16 out of 18 C1 genotypes were the wild relatives), this result was consistent with previous analysis, conducted from transpiration data of the wild and cultivated germplasm [61]. It also reinforced the inferences obtained from featureengineering based identification of genotypic differences (Fig.…”
Section: Quantifying Genotypic Differences In the Water-saving Traitsupporting
confidence: 90%
See 1 more Smart Citation
“…Since C1 was mostly composed of the wild genotypes (i.e. 16 out of 18 C1 genotypes were the wild relatives), this result was consistent with previous analysis, conducted from transpiration data of the wild and cultivated germplasm [61]. It also reinforced the inferences obtained from featureengineering based identification of genotypic differences (Fig.…”
Section: Quantifying Genotypic Differences In the Water-saving Traitsupporting
confidence: 90%
“…For instance, the wild germplasm had a flatter response i.e. had lower water loss during high VPD conditions than the highTE and lowTE ones, which was expected [61]. In addition, this flatter profile was congruent with the hypothetical model of the water-saving trait, illustrated in Fig.…”
Section: Preliminary Analysis Of Genotypic Differences From Et R and supporting
confidence: 68%
“…Modified photothermal units have been previously reported from this data set (von Wettberg et al., ), and flowering time models are being developed to explore associations of particular single nucleotide variants that segregate in the wild populations with phenology in common garden settings (Kozlov et al., ). We did not detect a significant correlation between the iButton temperature minima and temperature minima from 1960–1990 in the field in Turkey ( r = 0.32, P = 0.22), likely due to microsite effects such as the canopy cover, slope, and aspects of sites, as well as water availability and soil water‐holding capacity during the growing season.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The model for wild chickpea collected by von Wettberg et al (2018) (R 2 = 0.97) showed that the genotype-by-environment interactions accounted for about 17.2 % of variation in time to flowering (Kozlov et al, 2019a).…”
Section: Resultsmentioning
confidence: 99%